Lies, love, and breakfast at Tiffany's - Wright, Julie, 1972- (Proper romance., 2018)
"When Silvia asks her former coworker, Ben, to help her finish editing a major film project, she has no idea that it will lead to love--or a lawsuit between their production studios. She must summon all her courage, grace, and style for a conversation with Ben at their favorite breakfast diner, Tiffany's, before the credits roll"--Provided by publisher.